Triphenylamine-based electroactive compounds: synthesis, properties and application to organic electronics - Rybakiewicz, Renata; Zagorska, Malgorzata; Pron, Adam (Chemical papers, 2017)
This review is devoted to low and high molecular mass electroactive materials containing triphenylamine (TPA) structural units. It is shown that by appropriate selection of C–C coupling methods, it is possible to obtain solution-processable, electroactive materials of tunable donor–acceptor properties, suitable for the use as active layers in p-channel or ambipolar field effect transistors, as hole-transporting layers and as electroluminophores in organic light-emitting diodes. Other applications involve their use as components of bulk heterojunctions in organic solar cells and dye-sensitized solar cells. Since TPA-based materials exhibit high electrochemical reversibility, they can also be technologically exploited as solution-processable electrochromic materials.